2016
DOI: 10.1159/000447467
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Phytotherapy for Acute Rhinosinusitis

Abstract: Herbal medicine is a promising alternative in the treatment of acute rhinosinusitis (ARS). We performed a systematic review for phytopharmaceutical treatments of ARS. A computerized search of databases (Cochrane Library, PubMed, and Scopus) up to 16 September 2015 was performed. Randomized controlled trials (RCTs) and controlled trials (CTs) were included and assessed using the Cochrane risk of bias tool. Seven trials on Pelargonium sidoides (EPs 7630, Umckaloabo®), Myrtol (GeloMyrtol® forte), BNO 1016 (Sinupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
0
7
0
8
Order By: Relevance
“…In consequence, the EPOS guidelines recommended their use in adult ARS. 1 A recent meta-analysis by Kock et al 24 has confirmed the efficacy of some herbal compounds such as EPs 7630, Myrtol, BNO 101, BNO 1016, CE and Esberitox. In the present study, an association was found between the use of CE and a shorter disease duration, suggesting CE be accepted by physicians as a treatment choice for ARS.…”
Section: Discussionmentioning
confidence: 98%
“…In consequence, the EPOS guidelines recommended their use in adult ARS. 1 A recent meta-analysis by Kock et al 24 has confirmed the efficacy of some herbal compounds such as EPs 7630, Myrtol, BNO 101, BNO 1016, CE and Esberitox. In the present study, an association was found between the use of CE and a shorter disease duration, suggesting CE be accepted by physicians as a treatment choice for ARS.…”
Section: Discussionmentioning
confidence: 98%
“…Until the 1990s, evidence for the use of herbal products in acute rhinosinusitis remained largely anecdotal. However, in the past 20 years, randomized controlled trials in rhinosinusitis have been performed with a number of herbal products [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the epidemiological data as well as expert opinions of the prominent world clinicians and scientists, ARS remains to be the leading disease in the outpatient practice, which significantly decreases the quality of life as well as makes a great socio-economic impact in society (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%